Diversity and abundance of birds devastating rice-growing in the town of Daloa and its outskirts (Centre-West, Cote d’Ivoire) - Allou, Dimitri Kouadio; Ahon, Dibie Bernard; Zean, Gnininte Maxime; Egnankou, Wadja Mathieu; Koffi, Bene Jean-Claude; Tano, Yao (European Scientific Journal, ESJ, 2024)
Rice devastating birds are responsible for many losses in rice fields around the world. In Côte d’Ivoire, data on these birds is almost non-existent in the interior of the country. A study on these birds was carried out from November to December 2019 in three rice fields (Zépréguhé, Abattoir and Kennedy) in the town of Daloa and its outskirts. The objective of this study was to know the population of these birds in this area. The main method used was the fixed-point, time-dependent counts or point-in-time abundance index (IPA) method. This yielded 2368 individuals of 41 species in 14 families of eight orders. The Shannon-Weaver diversity (H’); equitability (E); dominance (IDO) and IPA indices of rice devastating birds in this zone are 3.03, 0.82, 24.79 and 135 respectively. The family best represented is that of the Ploceidae with 12 species and 882 individuals. The Village Weaver Ploceus cucullatus and the Northern Grey-headed Sparrow Passer griseus represent the two most abundant species with numbers of 368 and 219 individuals respectively. Of the three study sites, the Zépréguhé site is the most important in terms of species richness (38 species), relative abundance (37.54%) and IPA (IPA= 156). Further studies are planned to monitor the diversity and population dynamics of these birds over the long term and to determine the extent of their impacts on rice production in this area.